Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T10:54:26+01:00
7/9 - x/2=3/2 - x/18 (*18)
18(7/9) - 18(x/2)=18(3/2)- 18(x/18)
2(7)-9(x)=9(3)-x
14-9x=27-x
-9x+x=27-14
-8x=13
x=-1i5/8


0,7x-3+ 1,1x = -2,1 +0,6
0,7x+1,1x=-2,1+0,6+3
1,8x=1,5
x=0,8(3)



x/5- 2/3 + 1,5 =x/10 - 3/5 +2x/3 (*30)
30(x/5)-30(2/3)+30(15/10)=30(x/10)-30(3/5)+30(2x/3)
6x-20+45=3x-18+20x
6x-3x-20x=-18-45+20
-17x=-43
x=2i9/17



x-1 / 3 +5 (x+3) = 2-x
x-1/3+5x+15=2-x (*3)
3x-3(1/3)+15x+45=6-3x
3x+15x+3x=6+1-45
21x=-38
x=-1i17/21



5+z / 2 - 2(2x+5)=2x-1
5+z/2-4x-10=2x-1 (*2)
10+z-8x-20=4x-2
z-8x-4x=-2-10+20
z-12x=0
-12x=-z
x=z/12
39 4 39